Drivers of private consumption in the era of financialisation: new evidence for European Union countries - Barradas, R. (Review of Keynesian Economics, 2022)
This paper provides an empirical assessment of private consumption in the era of financialisation, using panel data for all 28 European Union countries from 1995 to 2019. According to the Post-Keynesian literature, there are two stylised facts: a fall in household labour income and an increase in both household debt and household financial and housing wealth. The two developments have opposite effects, with the former lowering private consumption and the latter increasing it. A Post-Keynesian private consumption equation is estimated by including four variables connected to those two stylised facts (household labour income, household debt, household financial wealth, and household housing wealth) and five additional control variables (lagged private consumption, short-term interest rate, long-term interest rate, inflation rate and unemployment rate). The results show that these two stylised facts have been detrimental to private consumption in the European Union countries as a whole, and more specifically in the euro area countries. The positive debt and wealth effects have not been sufficient to compensate for the negative labour income effect. The fall in household labour income has been the greatest constraint on the evolution of private consumption in the euro area countries.